2015
DOI: 10.3109/02688697.2015.1096906
|View full text |Cite
|
Sign up to set email alerts
|

Practises and controversies in the management of asymptomatic aneurysms: Results of an international survey

Abstract: Despite large trials supporting the management of small asymptomatic aneurysms, most neurosurgeons internationally chooses to treat them with surgery or endovascular means. Since clinicians use a number of factors beyond the maximum diameter when considering treatment options, future trials should consider these factors in their design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The development of a true rupture predictor requires longitu- dinal follow-up of unbiased cohorts of UIAs for a sufficiently long time, which is extremely difficult to accomplish because most UIAs eventually receive treatment. 19 Conversely, RRS is derived from consecutively collected cross-sectional data and therefore is unbiased. In current clinical practice, UIAs with an irregular or elongated shape and blebs, which are common features of RIAs, are usually recommended for treatment, regardless of size.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a true rupture predictor requires longitu- dinal follow-up of unbiased cohorts of UIAs for a sufficiently long time, which is extremely difficult to accomplish because most UIAs eventually receive treatment. 19 Conversely, RRS is derived from consecutively collected cross-sectional data and therefore is unbiased. In current clinical practice, UIAs with an irregular or elongated shape and blebs, which are common features of RIAs, are usually recommended for treatment, regardless of size.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a 2015 international survey of 203 neurosurgeons, most endorsed treatment of all asymptomatic aneurysms regardless of size. 12 A more recent North American study showed that 11% of treating physicians always or usually recommended treatment of the anterior circulation aneurysms of Ͻ5 mm without a family or personal history of SAH. 13 Another 30% sometimes treated these small aneurysms (40%-60% of the time).…”
Section: Discussionmentioning
confidence: 99%
“…9,11 An increasing number of treating physicians favor preventive treatment of even tiny aneurysms. 12,13 The American Heart Association/American Stroke Associa-tion (AHA/ASA) guidelines for management of patients with UIAs were updated in 2015. 8 However, these do not specify separate recommendations for small (3-7 mm) and tiny aneurysms (Յ3 mm), though their natural history, risk of rupture, and success of treatment might be different from aneurysms measuring Ͼ7 mm.…”
mentioning
confidence: 99%
“…In a 2015 international survey of 203 neurosurgeons, most endorsed treatment of all asymptomatic aneurysms regardless of size. 18 A more recent study showed that 11% of treating physicians always or usually recommend treatment of anterior circulation aneurysms measuring less than 5 mm without a family or personal history of SAH. 19 Another 30% of physicians treated these small aneurysms 40% to 60% of the time.…”
mentioning
confidence: 99%